Magyar felderítő a Krímben 1920-ban. Dokumentumközlés. I. rész - Kolontári, Attila (Acta Scientiarum Socialium, 2012)
In the course of 1920 the Hungarian political and military leadership was intensely interested in the developments in the Crimean situation, where the White Russian movement was fighting the last rear-guard fights headed by General Pyotr Vrangel against the Red Army. For Hungary, having lost World War I and being isolated and subjected to military control, there was no possibility to establish relations with the Vrangel-regime legally. Therefore, through various illegal channels, they sent military intelligence agents to the Crimea, who met the prominent members of that regime on the spot and were able to gather first-hand information from them. One of the Hungarian intelligence agents who made it to the Crimea was Lieautenant György Purjesz, who prepared a detailed report on his journey after his return. Although his report was highly evaluated by the Ministry of National Defence, its elements could not be utilized in practice since in the meantime the Vrangel-regime had failed and the Crimean peninsula had been evacuated by the Whites. In spite of this, the lengthy document contains a lot of noteworthy details relating to the history of the Russian civil war.
Keywords: Hungary; the Crimea; Vrangel-regime; Hungarian Intelligence Service; Lieutenant György Purjesz